Analisis Kinerja Kredit Lembaga Perkreditan Desa Di Kecamatan Gianyar Tahun 2011 - Gatrianingsih, Ni Luh Suci; Apriliani, Putu Desy (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
Since 1986, Bali was development village credits institutions at among the custom villages. Village Credits Institution is one of microfinance institutions, has intermediated fuction which accepted savings and giving credits are from and to society. This study was conducted to determine the effect and how strong the correlation amount of savings, deposits, and capital base of the credit performance of Village Credit Institutions in Gianyar District. Entire Gianyar District Village Credit Institutions as the research object. Testing was done by using a canonical correlation analysis. The study found that the amount of savings, deposits, and capital base has a correlation with the credit performance Village Credit Institutions in Gianyar district. The amount of savings has the strongest correlation with the performance of credit.
Keywords: Savings; Deposits; Capital Base; Village Credit Institutions